Emerging concerns in sustainability reporting: Disclosure of tertiary effects in the home appliance industry - Utkuhan Genc; Kendrick Hardaway; Nancy E. Landrum; John Mulrow (Cleaner and Responsible Consumption)
Home appliances like refrigerators, washers, and dryers have grown rapidly worldwide, contributing to significant ecological impacts across their life cycle. Part of the corporate response to ecological concerns has been to better document and report impacts via Sustainability Reporting (SR), which follows various global standards but often lacks specificity, particularly in capturing beyond direct (tertiary) effects. Our review asks how well and to what extent sustainability reporting covers these emerging “tertiary effects”, in home appliance industry. We assess all 26 available SRs from 254 major home appliance brands (representing 50 conglomerate companies), to assess how well they cover tertiary effects including: measurement of Scope 3 greenhouse gas emissions, attention to the nine planetary boundaries, and estimation and discussion of potential rebound effects. Only 23% of reports mention rebound effects, often framed as beneficial due to increased product demand, without addressing the negative implications of expanded resource use. Just one report covers all nine planetary boundaries, and relevant Scope 3 emissions, such as emissions from product use, are mentioned in less than half of the reports. The findings point to many opportunities for companies to disclose tertiary impacts. We draw on existing SR literature and examples from the reviewed SR reports to suggest ways for corporate self-reporting to better reflect ecological realities further afield from direct production operations. To improve SR, companies should acknowledge potential rebound effects from efficiency gains and follow guidelines to address a wider range of planetary boundary impacts and Scope 3 emissions beyond climate and freshwater concerns.